1988
DOI: 10.1002/1097-0142(19881201)62:11<2287::aid-cncr2820621103>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of CA 19-9 antigen level in the early detection of pancreatic cancer: A prospective study of 866 patients

Abstract: To establish if CA 19-9 could detect early pancreatic cancer, we measured its serum concentration in 866 patients admitted for benign diseases and observed for 2 years. All patients with an elevated CA 19-9 level (greater than 40 units (U)/ml) were submitted to a computed tomography (CT) scan of the pancreas. The CA 19-9 level was increased in 117 patients. One hundred fifteen of these 117 patients had false-positive elevations. The CA 19-9 concentration was elevated mostly in benign hepatobiliary diseases. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
3

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(38 citation statements)
references
References 23 publications
0
35
0
3
Order By: Relevance
“…3,4 In the series by Homma and Tsuchiya, 4 mass screening of 10,162 patients age Ͼ 40 years yielded only 4 patients (0.04%) with pancreatic carcinoma using serum CA19-9 and elastase-1 in combination with ultrasonography, whereas 85 of 4506 outpatients (1.9%) with gastrointestinal complaints or jaundice had pancreatic carcinoma. Many reports emphasized the correlation between pancreatic carcinoma and diabetes mellitus, [5][6][7][8] but pancreatic carcinoma is not frequent, even in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 In the series by Homma and Tsuchiya, 4 mass screening of 10,162 patients age Ͼ 40 years yielded only 4 patients (0.04%) with pancreatic carcinoma using serum CA19-9 and elastase-1 in combination with ultrasonography, whereas 85 of 4506 outpatients (1.9%) with gastrointestinal complaints or jaundice had pancreatic carcinoma. Many reports emphasized the correlation between pancreatic carcinoma and diabetes mellitus, [5][6][7][8] but pancreatic carcinoma is not frequent, even in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ERP was used as a gold standard for the diagnosis of pancreatic carcinoma despite its invasiveness, 9 because no other prospective studies using noninvasive diagnostic modalities have achieved acceptable results. 3,4 …”
mentioning
confidence: 99%
“…Also, in patients with chronic pancreatitis, the most important control group for pancreatic cancer, the specificity of CAM 17.1 was significantly higher than the specificity of CA 19-9 (90% and 78%; P>0.05). The combined evaluation of CAM 17.1 and CA 19-9 in patients with pancreatic cancer or chronic 10 000 (Frebourg et al, 1988;Haglund et al, 1986;Lucarotti et al, 1991;Magnani et al, 1983;Ohshio et al, 1990;Von Rossen et al, 1993;Safi et al, 1986;Toshkov et al, 1994). The monoclonal antibody CAM 17.1 detects a mucus glycoprotein with a high specificity for intestinal mucus, particularly in the colon, small intestine, biliary tract and pancreas (Makin et al, 1984;Raouf et al, 1991).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Mucins are also often detectable in the serum of patients suffering from pancreatic cancer; these include the blood group antigen sialylated Lewisa, which is the epitope for the antibody detecting CA19-9 (Magnani et al, 1983) and ThomsenFriedenreich antigen (galactose , Rhodes, 1988, 1990), which is the epitope for the lectin peanut agglutinin (PNA). Many reports have evaluated the practicality of using tumour markers such as CA19-9, CEA, CA50, CA242, CA494 and others for the serological diagnosis of pancreatic cancer and the follow-up of patients after tumour resection for pancreatic cancer (Frebourg et al, 1988;Freiss et al, 1993;Habib et al, 1986;Haglund et al, 1986;Kalser et al, 1978;Lucarotti et al, 1991;Nilsson et al, 1992;Ohshio et al, 1990;Von Rosen et al, 1993;Safi et al, 1986;Toshkov et al, 1994). In 1992, Parker et al firstly reported a new enzyme-linked antibody sandwich assay (CAM 17.1/WGA) using the monoclonal antibody CAM 17.1, which was generated after immunisation with Coll 2 -23 colorectal cancer cells.…”
mentioning
confidence: 99%
“…In addition, patients who are negative for Lewis antigen A or B (∼10% of patients with PDA) do not synthesize CA 19-9 and have undetectable levels, even in the advanced stages of the disease. 24 A promising discovery of biomarkers for the early diagnosis of PDA came from a serological proteome approach, which identified autoantibodies as a potential diagnostic marker in patients with PDA, in a genetically engineered mouse (GEM) model of PDA and in a prediagnostic cohort. These autoantibodies recognize the cytoskeletal protein Ezrin 25 and the phosphorylated α-enolase (ENO1), a glycolytic enzyme, which also functions as a plasminogen receptor.…”
mentioning
confidence: 99%